Habitat establishment, captive breeding and conservation translocation to save threatened populations of the Vulnerable European mudminnow Umbra krameri. Issue 4 (30th November 2016) - Tatár, Sándor; Bajomi, Bálint; Specziár, András; Tóth, Balázs; Müllerné Trenovszki, Magdolna; Urbányi, Béla; Csányi, Béla; Szekeres, József; Müller, Tamás
Abstract: In Europe 37% of freshwater fish are threatened. However, conservation activity is less widespread for fish compared to other vertebrate groups. The Vulnerable European mudminnow Umbra krameri is a marshland fish endemic to the Carpathian Basin. Its range and population have declined significantly since the 1990s. The main threats to the species are habitat loss and the invasive Chinese sleeper Perccottus glenii . During 2008–2012 a species conservation programme was established to rescue broodstocks from threatened populations, breed them under controlled conditions, translocate both rescued fish and their laboratory-reared offspring to surrogate habitats, and finally reintroduce offspring to their original habitats. Broodstocks from three threatened habitats were bred in the laboratory and produced offspring appropriate for stocking. Six artificial ponds were created in the pilot study area according to the environmental needs of the species, four of which proved to be suitable surrogate habitats in which translocated fish survived and reproduced successfully. Populations in the original habitats were supplemented with fish from laboratory breeding and from the natural recruitment of surrogate habitats, with special care of the corresponding broodstocks. Future challenges include improving our knowledge about the ecological processes in which the European mudminnow participates, identifying the most threatened populations, habitats suitable for restoration and potential areas for creation of surrogate habitats, and enhancing induced propagation methodology.